ChemInform Abstract: Application of Pulse Radiolysis to Mechanistic Investigations of Water Oxidation Catalysis. Issue 12 (25th March 2014) - Polyansky, Dmitry E.; Hurst, James K.; Lymar, Sergei V.
Abstract Review: <50 refs.